PENGARUH WORK-LIFE BALANCE TERHADAP KINERJA PADA KARYAWAN PT X - Widyastuti, Dea Putri; Fahlevi, Reza; Basaria, Debora (PSIKOLOGI KONSELING, 2024)
High productivity is expected to produce efficient and effective work. High productivity is needed for companies whose focus is producing goods, PT X is one of the companies whose focus is producing SIM Card and vouchers. In measuring success, human resources are the main factor that ensures the sustainability of the organization. One of the most important issues related to human resources is performance, performance is a reference for every company or organization to evaluate the continuity in achieving the goals of the company or organization. So that the easier it is for the company to achieve its goals, the better the performance of the employees there and vice versa. Work-life balance is one of the factors that can affect employee performance. This research approach uses quantitative methods as a research method with participants totaling 205 employees. The Work-life Balance Scale and Individual Work Performance Questionnaire (IPWQ) measuring instruments were used in this study. The data analysis process uses the IBM SPSS Statistic 25.0 application to test descriptive statistics of respondents and descriptive variables, validity test (R), reliability test (α), and linear regression test/hypothesis test (T). The results obtained work-life balance has an effect of 6.8% on employee performance, with a sig value of 0.000 <0.05.